Characterization of Fusobacterium varium Fv113-g1 isolated from a patient with ulcerative colitis based on complete genome sequence and transcriptome analysis - Sekizuka, Tsuyoshi; Ogasawara, Yumiko; Ohkusa, Toshifumi; Kuroda, Makoto (PloS one, 2017)
Fusobacterium spp. present in the oral and gut flora is carcinogenic and is associated with the risk of pancreatic and colorectal cancers. Fusobacterium spp. is also implicated in a broad spectrum of human pathologies, including Crohn's disease and ulcerative colitis (UC). Here we report the complete genome sequence of Fusobacterium varium Fv113-g1 (genome size, 3.96 Mb) isolated from a patient with UC. Comparative genome analyses totally suggested that Fv113-g1 is basically assigned as F. varium, in particular, it could be reclassified as notable F. varium subsp. similar to F. ulcerans because of partial shared orthologs. Compared with the genome sequences of F. varium ATCC 27725 (genome size, 3.30 Mb) and other strains of Fusobacterium spp., Fv113-g1 possesses many accessary pan-genome sequences with noteworthy multiple virulence factors, including 44 autotransporters (type V secretion system, T5SS) and 13 Fusobacterium adhesion (FadA) paralogs involved in potential mucosal inflammation. Indeed, transcriptome analysis demonstrated that Fv113-g1-specific accessary genes, such as multiple T5SS and fadA paralogs, showed notably increased expression with D-MEM cultivation than with brain heart infusion broth. This implied that growth condition may enhance the expression of such potential virulence factors, leading to remarkable survival against other gut microorganisms and to the pathogenicity to human intestinal epithelium.